2015
DOI: 10.1007/s11738-015-1823-x
|View full text |Cite
|
Sign up to set email alerts
|

Root-applied brassinolide can alleviate the NaCl injuries on cotton

Abstract: Brassinolide (BL) is a plant growth regulator. This study analyzes the effects of BL on cotton growth, Na ? accumulation, proline content, MDA content, antioxidant enzyme activities, and differentially expressed genes (DEGs) of cotton roots under NaCl stress. We grew two cotton cultivars, Sumian 12 (salt sensitive) and Sumian 22 (salt tolerant), in continuously aerated Hoagland's nutrient solution supplemented with 200 mM NaCl. NaCl stress increased the Na ? , proline, and MDA content and decreased root activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…In this manner, DPI, EBL and Pro, particularly Pro, lower the ROS in As-stressed tissues. This is in accordance with the reports of Ye et al (2012), Shu et al (2015), Singh et al (2015) and Chandrakar et al (2017a) under different abiotic stresses. Arsenic-impelled alterations in lipid moieties of Glycine max L. were analyzed by measuring contents of both MDA and HNE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this manner, DPI, EBL and Pro, particularly Pro, lower the ROS in As-stressed tissues. This is in accordance with the reports of Ye et al (2012), Shu et al (2015), Singh et al (2015) and Chandrakar et al (2017a) under different abiotic stresses. Arsenic-impelled alterations in lipid moieties of Glycine max L. were analyzed by measuring contents of both MDA and HNE.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that DPI directly scavenges ROS or decelerates the ROS generation process via inhibiting O 2˙ˉ synthase enzyme (Ye et al 2012). Similarly, EBL and Pro provide tolerance to oxidative stress either by accumulating endogenous osmolytes or activating antioxidant defense mechanism or both in the stressed tissues (Agami 2014, Shu et al 2015. In this manner, DPI, EBL and Pro, particularly Pro, lower the ROS in As-stressed tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are mediated by BR-induced genes, including defense genes and genes that can detoxify ROS produced in plants experiencing abiotic stress [ 15 ]. Exogenous BR application enhanced salinity stress tolerance enhancement in a variety of crop species [ 14 , 20 ]. Treatment with 24-epibrassinolide (EBL) reduced the salt-stress-induced inhibition of seed germination in Arabidopsis thaliana , Brassica napus , and Cucumis sativus [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since in vitro culture systems have been successfully applied to produce virus-free seed potatoes, they could also be used to screen for salt tolerance. Although many studies demonstrated a positive effect of BRs application on plant tolerance to salt stresses [ 20 , 28 , 29 ], BRs stimulate root growth at low concentrations but are inhibitory at higher concentrations [ 30 32 ]. The roles of BRs, however, in adventitious root growth are rarely understood in tissue culture systems.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological, biochemical, and molecular analyses have been performed to analyse the effects of BRs. However, detailed analyses should be performed to investigate the relationship between abiotic stresses and BRs, especially gene expression studies will provide knowledge about interaction at molecular level in plants [152]. We tried to cite as many papers as possible.…”
Section: Resultsmentioning
confidence: 99%